Kebijakan Pemerintah terhadap Pelaksanaan Majelis Taklim Di Banjarmasin - Yusna Zaidah; Arie Sulistyoko; Ibnu Haikal Jabbar (JOURNAL OF ISLAMIC AND LAW STUDIES, 2022)
bstract: During the pandemic, Majelis ta'lim, which is one form of community-based worship, is encountering difficulties in its execution. The actions of the majelis ta'lim, or collective meetings of many masses, create potential for inconsistencies between field conditions and those that should be governed by policy, resulting in activities that are supposed to be safe instead risking Covid-19 transmission.The theory of the policy application model, which includes communication, resources, tendencies, and ideal bureaucratic structures for the creation of successful policy implementation, was not completely fulfilled in the implementation of the policy for accelerating the handling of Covid-19 during the pandemic at the majelis ta'lim in the city of Banjarmasin during the pandemic. Starting with a lack of communication, the availability of resources, both adequate staff and clear and detailed information on the implementation, the organizers' authority that has yet to be fully maximized, and facilities that are not supportive, the organizers' and congregation's characteristics, and the implementation of technical procedures that have yet to be fully implemented. This occurred as a result of difficulties on the field caused by elements of the organizers and the majelis ta'lim congregation. Abstrak: Majelis ta’lim yang merupakan salah satu bentuk implementasi kegiatan peribadatan oleh masyarakat kini mengalami tantangan dalam penyelenggaraannya di masa pandemi. Kegiatan majelis ta’lim yang kolektif dengan banyak massa membuka peluang untuk terjadinya ketidaksesuian antara keadaan lapangan dengan yang seharusnya diatur kebijakan, sehingga kegiatan yang diharapkan dapat berlangsung dengan aman justru dapat beresiko terjadi penularan Covid-19. Penerapan kebijakan percepatan penanganan Covid-19 selama pandemi pada majelis ta’lim di kota Banjarmasin dilihat dari teori model penerapan kebijakan yang meliputi komunikasi, sumber daya, kecenderungan dan struktur birokrasi yang ideal untuk terciptanya keberhasilan penerapan kebijakan ternyata tidak terpenuhi secara menyeluruh. Mulai dari kurangnya komunikasi, ketersediaan sumber daya baik itu staf yang memadai, Informasi penyelenggaraan yang jelas dan rinci, kewenangan penyelenggara yang masih belum maksimal, dan fasilitas yang kurang mendukung, kemudian karakteristik penyelenggara maupun jemaah, serta penerapan teknis prosedur yang belum sepenuhnya. Hal ini terjadi dikarenakan adanya kendala di lapangan yang disebabkan oleh unsur penyelenggara dan jemaah majelis ta’lim.